Strategy of Education Needs Fulfillment for Children of Indonesian Migrant Workers in the Inter-Country Border Area - Raharjo F., Tyas Eko (Jurnal Penelitian Kesejahteraan Sosial, 2018)
This study describes the strategy of fulfilling the children educational needs of Indonesian Migrant Workers (TKI) in the country-to-country border areas. The research was conducted in Sebatik Tengah sub-district, a border area facing directly to Malaysia. The strategy of fulfilling the children educational needs of TKI is both beneficial either for parents who work as TKI and for local government policy makers in formulating programs to meet the educational needs of children. This study used a qualitative approach and was based on inductive pattern of thinking. The qualitative approach emphasized more on the meaning rather than that of generalization, data was collected through observation, interview, and documentation techniques. Data was analyzed descriptively and qualitatively. The results showed that there were three strategies of fulfilling the children educational needs of Indonesian Workers (TKI) in the border areas of Sebatik Tengah sub-districts, namely the strategy of fulfilling the needs of institution-base education, of family-base, and that of community-base. These three strategies can provide the services for Indonesian Workers (TKI) children in fulfilling their educational needs. It is hoped that the local government is able to construct and to formulate children protection program for Indonesian migrant labor by considering their educational needs and rights.